Analyzing murine Schwann cell development along growing axons - Heermann, Stephan; Krieglstein, Kerstin (JoVE. Video journal, 2012)
Here we describe a Schwann cell (SC) migration assay in which SCs are able to develop along extending axons.
Enthält auch Textversion
Gesehen am 23.10.2018
Wissenschaftlicher Film. Deutschland. 2012
Keywords: Film